Supramolecular Photonic Elastomers with Brilliant Structural Colors and Broad‐Spectrum Responsiveness. (24th February 2020) - Li, Miaomiao; Tan, Haiying; Jia, Lizhen; Zhong, Rui; Peng, Bolun; Zhou, Jiacheng; Xu, Jiangping; Xiong, Bijin; Zhang, Lianbin; Zhu, Jintao
Abstract: Photonic elastomers (PEs) that can tune their colors through adjusting the lattice spacing of incorporated colloidal particles during mechanical deformation have shown great promise in visualized strain/stress sensors. However, the unsatisfactory structural color and narrow‐spectrum responsiveness limit their broad applications. Herein, carbon‐coated Fe3 O4 nanoparticles (Fe3 O4 @C NPs) with a high refractive index (RI) and broad light absorption are employed for the construction of PEs with brilliant colors and broad‐spectrum responsiveness by incorporating the Fe3 O4 @C NPs into amino‐terminated poly(dimethylsiloxane) (amino‐PDMS) polymer through supramolecular interactions. The inherent light‐absorbing property, high RI, and supramolecular‐induced short‐range ordered arrangement of Fe3 O4 @C NPs imparts the PEs with brilliant and angle‐independent structural color. By optimizing the content of Fe3 O4 @C NPs in the PEs, broad‐spectrum responsiveness (stopband shifting ≈223 nm) and excellent recovery properties under a large strain can be achieved. The dynamic and reversible interaction endows the PEs with a healable capability. More interestingly, the incorporated Fe3 O4 @C NPs with photothermal capability can effectively absorb light and convert it into heat under light irradiation (solar light or near‐infrared laser), accelerating healing of the damaged PEs. This study provides a new strategy for bioinspired construction of PEs for applications in the fields of sensing, colorful coating, and display. Abstract : Photonic elastomers with brilliant structural colors and broad‐spectrum responsiveness are prepared by incorporating carbon‐coated Fe3 O4 nanoparticles (NPs) into amino‐terminated poly(dimethylsiloxane) via supramolecular interaction. The inherent light‐absorbing property, high refractive index, and isotropic arrangement of NPs endow the elastomers with brilliant and angle‐independent structural color and broad‐spectrum responsiveness for visualized sensors.